O-290 Cumulative live birth rates in a freeze-all and fresh transfer strategy after one complete ART cycle in ovulatory women. (30th June 2022) - Stormlund, S; Sopa, N; Zedeler, A; Jeanette, B; Prætorius, L; Nielsen, H.S; Klajnbard, A; Mikkelsen Englund, A.L; Laczna Kitlinski, M; La Cour Freiesleben, N; Polyzos, N.P; Bergh, C; et al.
Abstract: Study question: Is the cumulative live birth rate(CLBR) similar following a freeze-all and fresh transfer strategy including nearly all subsequent frozen-thaw cycles from the same oocyte retrieval? Summary answer: The chance of at least one live birth after use off all fresh and frozen blastocysts is similar following a freeze-all and fresh transfer strategy What is known already: Traditionally, ART success rates have been reported as pregnancies per fresh cycle or per embryo transfer. Advancements such as blastocyst culture and vitrification have enhanced survival and improved live birth rates. This facilitates single blastocyst transfer, a steadily increasing use of vitrified-warmed transfers, and a growing implementation of elective freeze-all cycles worldwide. Hence CLBRs, defined as the proportion of deliveries with at least one live birth following the use of all fresh and frozen embryos derived from one ovarian stimulation cycle, constitutes a better measure of IVF treatment success providing an all-inclusive success rate for ART. Study design, size, duration: CLBR was a secondary outcome in a multicentre randomised trial with allocation 1:1 to (A) Freeze-all strategy involving GnRH agonist trigger and single vitrified-warmed blastocyst transfer in consecutive modified-natural FET cycles or (B) Fresh transfer strategy with hCG trigger and fresh single blastocyst transfer followed by consecutive single blastocyst FET cycles. The minimum follow-up time from the start of ovarian stimulation was 2 years. Participants/materials, setting, methods: 460 women initiating their 1., 2. or 3. ART cycle at eight different clinics in Denmark, Sweden and Spain. The GnRH antagonist protocol and modified-natural frozen-thaw cycles with single blastocyst transfer were applied. Cumulative live birth was defined as at least one live birth per woman after all fresh and/or frozen cycles from a single ovarian stimulation. Women were followed until the first live birth. Analyses were performed according to the ITT principle. Main results and the role of chance: Baseline and treatment-related characteristics were similar between the two groups and a similar proportion of women had additional frozen-thawed embryo transfers following the initial fresh or frozen transfer. Combining all fresh and/or frozen transfers from the included oocyte retrieval with a minimum of 2-years of follow-up, the cumulative live birth rate was 42.6% (95/223) in the freeze-all group versus 41.7% (96/230) in the fresh transfer strategy group (risk ratio (RR): 1.0; 95%CI 0.87-1.19, P = 0.93). The median (IQR) time to first pregnancy was 106.0 (80.5-156.5) versus 29.0 (27.0-113.5) days in the Freeze all and Fresh transfer group, respectively. Of all subsequent frozen transfers, a total of 34/103 (33%) cycles resulted in a live birth in the freeze all group compared with 29/108 (26.9%) in the fresh transfer group (risk ratio (RR): 1.09; 95% CI 0.91-1.3; P = 0.41). Finally, a total of three (1.3%) and eight (3.5%) blastocysts in the freeze all and fresh transfer strategy group respectively, did not survive the freezing thawing process (p = 0.24). The number of women with unused cryopreserved embryos at the end of the 2-year follow-up period was four (0.9%) in the freeze all and seven (1.6%) in the fresh transfer group. Limitations, reasons for caution: The primary RCT outcome was ongoing pregnancy rate following two treatment strategies within the ART regimen hence two different ovulation trigger modalities were applied, introducing a risk of bias. Furthermore, despite a 2-year follow-up few women (2.4%) still had cryopreserved embryos and no live birth at the end of follow-up. Wider implications of the findings: Advancements of embryo culture and freezing-thawing techniques facilitate an elective single embryo transfer policy. CLBRs provide an all-inclusive success rate for ART. A freeze-all strategy can be used as an alternative to a fresh transfer strategy in women at risk of OHSS as CLBRs are similar. Trial registration number: NCT02746562